[18F]‐labeled positron emission tomography ligand for the histamine H4 receptor. (15th June 2021) - Zak, Agnieszka; Lemaire, Lucas; Chalon, Sylvie; Chicheri, Gabrielle; Marzag, Hamid; Bodard, Sylvie; Sérrière, Sophie; Routier, Sylvain; Buron, Frédéric; Vercouillie, Johnny
Abstract : We synthesized 5‐[ 18 F]‐fluoro‐1 H ‐indol‐2‐yl)(4‐methyl‐1‐piperazinyl)methanone ([ 18 F]5 ) via a Suzuki approach starting from a protected pinacol borane precursor followed by acidic hydrolysis of the t ‐Boc protecting group. The non‐optimized radiochemical yield was 5.7 ± 1.35%, radiochemical purity was over 99%, and molar activity was 100.7 ± 34.5 GBq/μmol ( n = 3). [ 18 F]5 was stable in rat plasma for at least 4 h and was evaluated by μPET imaging and biodistribution using a unilateral quinolinic acid rat model of neuroinflammation. The time‐activity curve showed that [ 18 F]5 entered the brain immediately after intravenous injection and then left it progressively with a very low level reached from 30 min after injection. The biodistribution study showed no difference in the accumulation of [ 18 F]5 between the lesioned and intact side of the brain and between control rats and animals pretreated with a saturating dose of JNJ‐7777120 as a specific H4R antagonist. Hence, despite its in vitro nanomolar affinity for H4R, and its ability to cross the blood–brain barrier in rats, [ 18 F]5 does not appear suitable to image in vivo the receptor by PET. Abstract : 5‐[ 18 F]‐Fluoro‐1 H ‐indol‐2‐yl)(4‐methyl‐1‐piperazinyl)methanone ([ 18 F]5 ) was radiolabeled and evaluated by biodistribution and µPET imaging in a quinolinic acid rat model of inflammation. No significant difference was observed between the ipsilateral and contralateral sides and between control and pretreated rats with a specific H4R antagonist. Thus, [ 18 F]5 does not appear suitable to image in vivo the H4R by PET.